3D printed collagen/silk fibroin scaffolds carrying the secretome of human umbilical mesenchymal stem cells ameliorated neurological dysfunction after spinal cord injury in rats. (24th February 2022) - Chen, Chong; Xu, Hai-Huan; Liu, Xiao-Yin; Zhang, Yu-Sheng; Zhong, Lin; Wang, You-Wei; Xu, Lin; Wei, Pan; Chen, Ya-Xing; Liu, Peng; Hao, Chen-Ru; Jia, Xiao-Li; et al.
Abstract: Although implantation of biomaterials carrying mesenchymal stem cells (MSCs) is considered as a promising strategy for ameliorating neural function after spinal cord injury (SCI), there are still some challenges including poor cell survival rate, tumorigenicity and ethics concerns. The performance of the secretome derived from MSCs was more stable, and its clinical transformation was more operable. Cytokine antibody array demonstrated that the secretome of MSCs contained 79 proteins among the 174 proteins analyzed. Three-dimensional (3D) printed collagen/silk fibroin scaffolds carrying MSCs secretome improved hindlimb locomotor function according to the Basso–Beattie–Bresnahan scores, the inclined-grid climbing test and electrophysiological analysis. Parallel with locomotor function recovery, 3D printed collagen/silk fibroin scaffolds carrying MSCs secretome could further facilitate nerve fiber regeneration, enhance remyelination and accelerate the establishment of synaptic connections at the injury site compared to 3D printed collagen/silk fibroin scaffolds alone group according to magnetic resonance imaging, diffusion tensor imaging, hematoxylin and eosin staining, Bielschowsky's silver staining, immunofluorescence staining and transmission electron microscopy. These results indicated the implantation of 3D printed collagen/silk fibroin scaffolds carrying MSCs secretome might be a potential treatment for SCI.